Psychosocial Workplace Hazards and Workers' Health in Factory Sector - Chan, Shiau Wei; R, Tasmin; Nor Aziati, A. H.; Rasi, Raja Zuraidah; Ismail, Fadillah; Ruslan, Rumaizah; R, Ramlan; Nojumuddin, Nur Syereena; Ahmad, M.F.; Omar, Siti Sarah; Zaman, Izzuddin; Anuar, Muhamad Fuad (International Journal of Integrated Engineering, 2018)
Nowadays, issues on psychosocial workplace hazards have become a hot topic. However, only a small amount of research has been conducted in Malaysia. The purpose of this study is to determine the relationship between psychosocial workplace hazards and workers' health which is measured using Body Mass Index (BMI) as well as mental health. Two research hypotheses related to psychosocial workplace hazards, i.e. Body Mass Index (BMI) and mental health were examined. In this study, 105 workers were selected randomly from factories located in Klang, Selangor, and questionnaires were distributed to them. The result revealed that there is a significant relationship between psychosocial workplace hazards and BMI, while there is no significant relationship between psychosocial workplace hazards and mental health. This study serves as a guideline for organisations concerning the relationship between psychosocial workplace hazards with workers' health.